RIGHT ON PECATU DESA LAND BASED ON THE PRINCIPLE OF THE STATEâS RIGHT TO CONTROL IN THE DIALECTICS OF JUSTICE AND LEGAL CERTAINTY - Husni, Anang (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
The right of possession by state is public domain, as for right of ulayat is collective domain whichis permanently referring to private domain. Therefore, to put Pecatu land as part of districtgovernmentâs property is illegal because district government is not an adat community; this toa norm of Indonesian constitution 1945 as referred to in article 33 (3) and article 18B (2).The criterion or the barometer of justice as stipulated in such articles is ââ¦â¦.shall be made usefor the greatest peopleâ should be given priority rather than legal certainty toward the right ofPecatu land.Keywords: The Right of Possession by State, Justice, Legal Certainty, Pecatu Land